2021
DOI: 10.2147/cmar.s300495
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective Effect of Quercetin and Sitagliptin in Doxorubicin-Induced Cardiac Toxicity in Rats

Abstract: Objective: A previous study revealed a pronounced protective effect of combining quercetin (QC) with sitagliptin (STN) in testicular tissue. Accordingly, this study was designed to evaluate the cardioprotective effects of QC and STN each alone or in combination in doxorubicin (DOX)-induced cardiotoxicity in the rats. Methodology: Thirty male adult Wistar rats were divided into five groups: the first group (control) treated with sodium chloride, the second group treated with DOX (3 mg/kg I. P. injection), the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 42 publications
2
10
0
Order By: Relevance
“…In addition, it was reported that treatments exhibiting antihyperlipidemic effects can decrease DXB-induced cardiotoxicity [ 26 , 27 ]. The administration of DXB was associated with significant increases in serum TG, TC and LDL-C, while HDL was markedly reduced, corroborating the findings of previous studies [ 24 , 25 ]. COST significantly ameliorated DOX-induced hyperlipidemia in the treated rats.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In addition, it was reported that treatments exhibiting antihyperlipidemic effects can decrease DXB-induced cardiotoxicity [ 26 , 27 ]. The administration of DXB was associated with significant increases in serum TG, TC and LDL-C, while HDL was markedly reduced, corroborating the findings of previous studies [ 24 , 25 ]. COST significantly ameliorated DOX-induced hyperlipidemia in the treated rats.…”
Section: Discussionsupporting
confidence: 90%
“…Several studies have shown the prominent role of lipids in cardiovascular diseases and the role of DXB-induced hyperlipidemia has been well documented [ 24 , 25 ]. DXB interferes with the metabolism and synthesis of lipids resulting in high serum and cardiac lipid profiles [ 9 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…DOX administration significantly elevated LDH and CK‐MB contents compared to the saline group, which has been reported in many investigations (Aygün & Gul, 2019; Momin et al, 2012; Ozdoğan et al, 2011; Yagmurca et al, 2003). Furthermore, it was shown that administration of DOX (3 mg/kg for 6 injections in 2 weeks, intraperitoneally) elevated the serum level of LDH in rats (Aziz, 2021). It has been suggested that DOX by decreasing oxygen or glucose supply can damage the membrane of the myocardial cell and result in leakage of cellular enzymes to blood flow (Momin et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…However, Dox induces apoptosis by generating high levels of ROS in tumor cells leading to lipid peroxidation, DNA damage, and the trigger of apoptosis [28]. Beside the apoptotic effect of STG, several studies reported its impact in halting some of the Dox-induced multiple organ toxicity including cardiotoxicity [53][54][55] and nephrotoxicity [56].…”
Section: Discussionmentioning
confidence: 99%